A thought that transcends. Peter Seixas and his contributions to the development of Historical Thought - Chávez Preisler, Carolina (2024)
In the early 1980s, Denis Shemilt proposed that history should be taught so that students can understand the past through the particular methods and perspectives of the discipline. His ideas were pioneering and triggering, so that in the future and in different latitudes, research groups are formed with the purpose of developing proposals that allow clarifying what these particular methods and perspectives are. In this line, Peter Seixas since the 1990s, has been one of the researchers who has contributed the most to clarifying these issues, leading the "historical thinking" research group in Canada and being a benchmark for other research. That is why, in this paper, it is proposed to reflect on the contributions of Peter Seixas' thought for the understanding of the teaching of history, of what it is and what it implies to think historically.